Causal relationship of cereal intake and type with cardiovascular disease: a Mendelian randomization study - Liu, Jianhui; Cai, Dihui (Frontiers in Nutrition, 2024)
Background Observational studies have suggested that cereal consumption is associated with a reduced risk of cardiovascular disease (CVD). However, the potential causal relationship is not clear. We aimed to investigate the association of cereal intake and cereal type with CVD risk. Methods Two-step Mendelian randomization (MR) analysis was performed to confirm the causal association of cereal intake and cereal type with the risk of several common CVDs. Furthermore, two-step MR analysis was used to explore the mediating effect of cardiovascular metabolic factors, and multivariable MR analysis was used to assess the impact of socioeconomic status, such as education and income, on the causal association. Results The MR analysis indicated that genetically predicted cereal intake is associated with reduced risk of large artery stroke (LAS) (odd ratio (OR): 0.421; 95% confidence interval (CI) [0.193, 0.918]; p = 0.030), and muesli as the primary cereal intake is associated with reduced risk of coronary heart disease (CHD) (OR: 0.100; 95% CI [0.023, 0.437]; p = 0.002), myocardial infarction (MI) (OR: 0.101; 95% CI [0.020, 0.509]; p = 0.005), heart failure (OR: 0.210; 95% CI [0.064, 0.684]; p = 0.010), ischemic stroke (IS) (OR: 0.130; 95% CI [0.029, 0.591]; p = 0.008), LAS (OR: 0.017; 95% CI [0.0004, 0.737]; p = 0.034), and small-vessel stroke (OR: 0.021; 95% CI [0.001, 0.708]; p = 0.005). In contrast, genetically predicted biscuits as the primary cereal intake increased the risk of CHD (OR: 6.557; 95% CI [1.197, 36.031]; p = 0.031), and other cereals, such as cornflakes, as the primary cereal intake increased the risk of CHD (OR: 3.803; 95% CI [1.194, 12.111]; p = 0.024), MI (OR: 4.240; 95% CI [1.185, 15.174]; p = 0.026), stroke (OR: 3.154; 95% CI [1.070, 9.298]; p = 0.037), and IS (OR: 3.736; 95% CI [1.185, 11.782]; p = 0.024). Multivariable MR analysis underscored the significant role of education and income in the causal association, and two-step MR analysis indicated that body mass index, lipids, and blood glucose exerted important mediating effects in the causal association. Conclusion The findings of our study underscore the causal beneficial influence of muesli as the primary cereal intake on CVDs. A reasonable consumption of muesli may provide primary prevention of CVDs.